2022
DOI: 10.3390/biom12010103
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Effects of Serum Calcium and Phosphate Levels and Their Ratio on Incident Ischemic Heart Disease among Korean Adults

Abstract: Serum calcium and phosphate levels are controlled by a regulatory system, but their individual concentration tendencies and interactions may affect long-term vascular health. This study aimed to assess the effects of serum calcium and phosphate levels on incident ischemic heart disease (IHD) in a large-scale community-dwelling Korean cohort. We evaluated 15,259 non-diabetic individuals (median age, 45 years; range, 30–85) without previous IHD or ischemic stroke using the Korean National Health Insurance data. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 40 publications
2
7
0
Order By: Relevance
“…Additionally, doxorubicin stimulates a reduction in the calcium storing amplitude of mitochondria and exacerbates calcium overload. In harmony with Jung et al [ 57 ], serum phosphorus levels showed elevation in our cardiotoxicity model. Hyperphosphatemia may result from doxorubicin's indirect toxic effects on the kidneys.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Additionally, doxorubicin stimulates a reduction in the calcium storing amplitude of mitochondria and exacerbates calcium overload. In harmony with Jung et al [ 57 ], serum phosphorus levels showed elevation in our cardiotoxicity model. Hyperphosphatemia may result from doxorubicin's indirect toxic effects on the kidneys.…”
Section: Discussionsupporting
confidence: 91%
“…These calcium ions induce free radicals production that is responsible for oxidative stress and subsequent cardiac dysfunction. This is in consent with many former studies [ 55 57 ] who proved the doxorubicin-induced calcium ions imbalance and overload. According to Mitry and Edwards [ 58 ], doxorubicin causes loss of calcium homeostasis by affecting the calcium pump found in the membrane and interfering with calcium reservation by the sarcoplasmic reticulum.…”
Section: Discussionsupporting
confidence: 89%
“…Hyperkalemia is also markedly related to poor prognosis in those patients and may influence survival (Toledo et al 2021 ). Other studies, like Jung et al ( 2022 ), reported increased Ca and P levels in heart failure. In the current study, DOXO intoxication did not alter Ca and P serum levels but showed marked increases in serum Na and K levels that might be due to DOXO-induced renal complications or/and neurohormonal disturbances behind cardiotoxicity pathogenesis.…”
Section: Discussionmentioning
confidence: 80%
“…After applying exclusion criteria, 16,455 individuals (8425 men and 8029 women) were included in the final analysis ( Figure 1 ). The materials and methodology of the HERAS-HIRA datasets were described in detail in previous studies [ 19 , 20 ]. UHR (%) was calculated as uric acid (mg/dL) divided by HDL cholesterol (mg/dL).…”
Section: Methodsmentioning
confidence: 99%